DYNAMICS OF THE RECRUITMENT PROCESS FOR WOMEN LEGISLATIVE CANDIDATES (A STUDY OF THE NASDEM PARTY IN THE 2024 LEGISLATIVE ELECTIONS) - Malindir, Gaston; Bayu Septiansyah (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2024)
The problem of this research lies in the recruitment process carried out by the West Java Province NasDem Party for female legislative candidate candidates in the 2024 General Election which tends to be closed and only provides opportunities to women with certain backgrounds. The aim of this research is to find out about the recruitment process for female legislative candidates by the West Java NasDem Party in the 2024 Legislative Election and what factors influence it. This research uses a qualitative approach with data collection techniques that include observation and literature study. The data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of this research show that; that; 1) In the process of recruiting female legislative candidate candidates for the 2024 elections, the West Java Province NasDem Party tends to be exclusive and closed in terms of deciding which female legislative candidate candidates will run. Data shows that the NasDem Party's female legislative candidates who are contesting in the XI electoral district in West Java are mostly dominated by businessmen, and are followed by party administrators. 2) There are several factors that influence the recruitment of female legislative candidate candidates by the West Java NasDem Party which include; Political parties are still neglectful in making decisions regarding women's aspirations, parties do not have a program to empower women cadres, patriarchal stigma makes support from the family or from the community still weak, limited access to capital to support women's activities in the political environment, and the inability to balance Maximum time for political activities in parliament.